Outdoor recreation’s association with mental health and well-being during the COVID-19 pandemic - Colby Parkinson; Xiangyou Shen; Megan MacDonald; Samuel W. Logan; Lydia Gorrell; Kreg Lindberg (PLoS ONE, 2025)
Outdoor recreation provided a crucial way to maintain physical activity, reduce stress, and preserve a sense of normalcy during the COVID-19 pandemic. This study assessed the relationship between outdoor recreation and mental health in the context of COVID-19. Cross-sectional online survey data were collected in early 2021 from a sample (n = 503) representative of the U.S. adult population in age, gender, and race. We observed prevalent engagement in near-home outdoor activities, widespread reductions in outdoor engagement relative to the pre-COVID period, and significant age, financial, and racial differences in engagement patterns. Regression models suggested that reduced outdoor recreation was associated with higher levels of perceived stress and depressive symptoms, whereas more frequent outdoor activities predicted better well-being. The health implications of adaptive engagement versus cumulative exposure during times of significant disruptions are discussed, along with the need to address structural inequities in accessing outdoor recreation as a health behavior.